The 2016 HIV diagnosis and care cascade in New South Wales, Australia: meeting the UNAIDS 90‐90‐90 targets. Issue 4 (20th April 2018) - Keen, Phillip; Gray, Richard T; Telfer, Barbara; Guy, Rebecca; Schmidt, Heather‐Marie; Whittaker, Bill; Holden, Jo; Holt, Martin; Kelleher, Anthony; Wilson, David; Callander, Denton; Cooper, David A; et al.
Abstract: Introduction: The HIV Strategy in New South Wales (NSW) Australia aims to virtually eliminate HIV transmission by 2020. We estimated the 2016 HIV diagnosis and care cascade for the state of NSW, with a focus on introducing population‐based data to improve data quality and assess progress towards the UNAIDS 90‐90‐90 targets. Methods: To estimate the number of people living with diagnosed HIV (PLDHIV) we used NSW data from the Australian National HIV Registry, enhanced by surveillance among people recently diagnosed with HIV to improve migration estimates. The number of undiagnosed PLHIV was estimated using back‐projection modelling by CD4 count at diagnosis. De‐duplicated prescription claims data were obtained from the Australian Pharmaceutical Benefits Scheme (PBS), and were combined with an estimate for those ineligible, to determine the number of PLDHIV on antiretroviral therapy (ART). Data from a clinic network with 87% coverage of PLDHIV in NSW enabled the estimation of the number on ART who had HIV suppression. Results and discussion: We estimated that 10, 110 PLHIV resided in NSW in 2016 (range 8400 to 11, 720), among whom 9230 (91.3%) were diagnosed, and 8490 (92.0% of those diagnosed) were receiving ART. Among PLDHIV receiving ART, 8020 (94.5%) had suppressed viral load (<200 HIV‐1 RNA copies/mL). Overall, 79.3% of all PLHIV had HIV virological suppression. Conclusion: NSW has met each of the UNAIDS 90‐90‐90 targets. The enhanced surveillance methods and data collection systems improved data quality. Measuring and meeting the 90‐90‐90 targets is feasible and could be achieved in comparable parts of the world.